Development of Bangle Rhizome and Purple Sweet Potato Flour Biscuit and Its in vivo Antioxidant Activity in High-Fat Diet-Induced Rats: Biscuit, hiperlipid and antioxidant - Nanik Sulistyani; Nurkhasanah Mahfudh; Rofidah Nur Umar; Muhammad Fathurrachman Mantali (Journal of Tropical Life Science, 2023)
Bangle rhizome and purple sweet potato could be used as functional food to overcome health problems such as hyperlipidemia. The anti-hyperlipidemic, nutritional properties of the above-said root vegetables could be formulated into a more community-preferred food in the form of biscuits. For this reason, this study aims to formulate biscuits from the mixed flour of bangle rhizome and purple sweet potato. Next, the prepared product's antioxidant activity and lipid-lowering properties are tested in vivo in high-fat diet-induced Wistar rats. In this study, bangle rhizome and purple sweet potato were turned into flour and formulated into three types of biscuits comprising different ratios of bangle rhizome and purple sweet potato flour (5:39 % w/w (F1), 3:41 % w/w (F2), and 2:42 % w/w (F3)). The study found that the baked products showed good organoleptic and physical properties, yielding golden- to brown-colored biscuits with a distinctive aroma and vaguely bitter after-taste, with F3 showing the highest hardness (8.94 0.18). The proximate analysis test showed that the biscuits achieved three of the six SNI 01-2973-2011 quality requirements. The best formula (F3) exhibited acceptable in vivo antioxidant catalase (5.12 0.16 U/mL) and glutathione peroxidase activity (64.44 2.11 U/mg) in high-fat diet Wistar rats tested for 28 days. The F3 formula was deemed the best, yielding biscuits with low moisture content and good crispiness. The formulated biscuits increased catalase's antioxidant activity (285.47%) and glutathione peroxidase (265.08%) more than the negative control. Hence, the study demonstrated that bangle rhizome and purple sweet potato-containing biscuits were potentially useful functional foods for improving antioxidant activity in high-fat diet-induced Wistar rats.